1996
DOI: 10.1101/gad.10.14.1724
|View full text |Cite
|
Sign up to set email alerts
|

Loss of plectin causes epidermolysis bullosa with muscular dystrophy: cDNA cloning and genomic organization.

Abstract: Plectin is a widely expressed high molecular weight protein that is involved in cytoskeleton-membrane attachment in epithelial cells, muscle, and other tissues. The human autosomal recessive disorder epidermolysis bullosa with muscular dystrophy (MD-EBS) shows epidermal blister formation at the level of the hemidesmosome and is associated with a myopathy of unknown etiology. Here, plectin was found to be absent in skin and cultured keratinocytes from an MD-EBS patient by immunofluorescence and immunoprecipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
1
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(222 citation statements)
references
References 52 publications
7
211
1
3
Order By: Relevance
“…We speculate that these multiple linkage systems play synergistic roles in maintaining the firm anchorage of keratin bundles to the hemidesmosome plaque. This idea is supported by studies that reveal that ablation of either plectin or BP230 in keratinocytes results in loss of keratin bundle association with the plaque of the hemidesmosome (Guo et al, 1995;Gache et al, 1996;McLean et al, 1996;Smith et al, 1996). These complex interconnections may enhance further the stability of keratin interaction with the cell surface and not only modulate cell-matrix association but also facilitate signal transduction at the site of the hemidesmosome (Giancotti, 1996).…”
Section: Discussionmentioning
confidence: 93%
“…We speculate that these multiple linkage systems play synergistic roles in maintaining the firm anchorage of keratin bundles to the hemidesmosome plaque. This idea is supported by studies that reveal that ablation of either plectin or BP230 in keratinocytes results in loss of keratin bundle association with the plaque of the hemidesmosome (Guo et al, 1995;Gache et al, 1996;McLean et al, 1996;Smith et al, 1996). These complex interconnections may enhance further the stability of keratin interaction with the cell surface and not only modulate cell-matrix association but also facilitate signal transduction at the site of the hemidesmosome (Giancotti, 1996).…”
Section: Discussionmentioning
confidence: 93%
“…Similar structures were found in cells of the mouse TA3/Ha carcinoma cell line that normally grows in suspension because the large amount of the mucin epiglycanin on their surface prevents attachment of the cells to the substratum (Kemperman 1992), and therefore these molecules may also associate in other cell types to form a complex for anchoring other cytoskeleton components to the plasma membrane. Recent evidence indicates that HD1 and plectin are similar or identical proteins (Gache et al, 1996;McLean et al, 1996;Smith et al, 1996). Plectin is considered to be a general cross-linker of cytoskeletal networks (Foisner and Wiche, 1991), and in COS-7 cells plectin has been shown to associate with the vimentin and keratin networks (Wiche et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The structure of HD1 has not yet been determined but its apparent molecular mass and tissue distribution are similar to fhose of plectin (Gache et al, 1996). In addition, mutations in the plectin gene correlate with a loss of immunoreactivity not only of plectin but also of HD1 (McLean et al, 1996;Smith et al 1996). Together, these data suggest that HD1 and plectin are identical or related molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Initial examination of biochemical and synthetic properties of cultured keratinocytes from patients with EB-MD using antibodies against plectin showed that this protein was completely absent in the cells of several patients with EB-MD, and subsequently, mutations in the plectin gene (PLEC1) could be demonstrated in a number of families [46][47][48][49]. While EB-MD is a rare autosomal recessive disorder, most of the mutations reported thus far result in premature termination codons on both alleles of plectin, either by nonsense, insertion/deletion or splicing mutations, and the phenotype in these patients is remarkably consistent manifesting with neonatal blistering and progressive muscle weakness from the first or second decade of life on.…”
Section: The Paradigm Of Plectin Disordersmentioning
confidence: 99%